2020
DOI: 10.1186/s13054-020-2778-x
|View full text |Cite
|
Sign up to set email alerts
|

ARDS Subphenotypes: Understanding a Heterogeneous Syndrome

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2020. Other selected articles can be found online at https://www.biomedcentral.com/collections/annualupdate2020. Further information about the Annual Update in Intensive Care and Emergency Medicine is available from http:// www.springer.com/series/8901.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 52 publications
0
102
0
3
Order By: Relevance
“…This means that, while renal complications are more likely in patients with pre-existing chronic impairment of kidney function, moderate-to-severe AKI can also be found in patients with normal serum creatinine levels these may represent a higher-risk subset of patients with ARDS. Wilson et al [109] noted that similar observations have been reported for COVID-19-associated ARDS, which could develop into AKI on average 9 days after admission together with secondary infections and acute cardiac damage [26]. In ARDS, patients age, severity of illness and the presence of diabetes are all risk factors for acute kidney injury.…”
Section: Clinical Features In Patients With Acute Kidney Injury (Aki)mentioning
confidence: 62%
“…This means that, while renal complications are more likely in patients with pre-existing chronic impairment of kidney function, moderate-to-severe AKI can also be found in patients with normal serum creatinine levels these may represent a higher-risk subset of patients with ARDS. Wilson et al [109] noted that similar observations have been reported for COVID-19-associated ARDS, which could develop into AKI on average 9 days after admission together with secondary infections and acute cardiac damage [26]. In ARDS, patients age, severity of illness and the presence of diabetes are all risk factors for acute kidney injury.…”
Section: Clinical Features In Patients With Acute Kidney Injury (Aki)mentioning
confidence: 62%
“…AKI represents a life-threatening complication in critically ill patients, often leading to increased risk of death. As recently reported by Wilson et al, the onset of moderate-to-severe AKI described a higher-risk subset of ARDS patients, with a significant risk for mortality [4]. Considering the possible pathogenic mechanisms of AKI-associated ARDS, AKI may be ascribed to different causes such as impairment of gas exchange, hemodynamic alterations including right heart failure, fluid overload and systemic congestion, injurious mechanic ventilation strategies, and development of secondary infections/sepsis.…”
Section: Main Textmentioning
confidence: 87%
“…Importantly, these studies have shown that ARDS is not a uniform disease, that it is heterogeneous and that this heterogeneity may be explored to enrich for specific outcomes [36] and help predict responses to different therapies.…”
Section: Ards Genomics and Transcriptomics Researchmentioning
confidence: 99%